MENINGKATKAN HIGHER ORDER THINKING SKILL DAN SIKAP TERBUKA MELALUI MEDIA PEMBELAJARAN ANDROID - Nugroho Prasetya Adi; Yohanes Kurniawan (JOURNAL OF KOMODO SCIENCE EDUCATION, 2018)
This study aimed to: (1) produce android learning media which was reasonable for physics learning in SMA, and (2) examine the effectiveness of android learning media to increase student's Higher Order Thinking Skills (HOTS) and open attitude. This research used R&D methods with 4D models consisting of (1) Define, (2) Design, (3) Developt, and (4) Disseminate. The resulted product is android learning media. The data were collected by using an observation sheet of learning media, a test of HOTS, a questionnaire of open attitude, questionnaire of student’s responses. The data were analyzed using the descriptive statistics, N-Gain analysis, multivariate test statistic Hotelling’s T2, and effect size analysis. The result of this research produced android learning media which: (1) was reasonable to increase students HOTS and open attitude with very good category based on expert, teachers, and good category based the response of students, and (2) effective to increase students HOTS and open attitude significantly by effect size analysis.